A global meta‐analysis of the impacts of no‐tillage on soil aggregation and aggregate‐associated organic carbon. (8th November 2021) - Liu, Xiaotong; Wu, Xueping; Liang, Guopeng; Zheng, Fengjun; Zhang, Mengni; Li, Shengping
Abstract: No‐tillage (NT) has been shown to control soil degradation by impacting soil aggregates (i.e., basic units of soil structure, whose characteristics mediate key soil processes, like carbon sequestration). However, there has been no systematic analysis of the impacts of NT on soil aggregation and aggregate‐associated soil organic carbon (SOC) at global level. We conducted a global meta‐analysis of 89 publications to elucidate the changes in soil aggregation and aggregate‐associated SOC under NT. Notably, we quantified the roles of diverse environmental and agronomic factors (e.g., climatic conditions, experimental duration, cropping intensity, soil texture, and initial SOC/pH) in the changes in those variables. Relative to conventional tillage (CT), NT significantly increased the proportions of water‐stable large (LM) and small (SM) macro‐aggregates and the mean weight diameter (MWD) (by 49%, 11%, and 23%, respectively) but decreased the proportions of micro‐aggregates (MIC) and silt plus clay‐size particles (SC) (by 11% and 16%, respectively). NT significantly enhanced SOC concentrations in LM (17%), SM (14%), MIC (10%), and SC (7%) compared to CT. Furthermore, the random forest (RF) model demonstrated that climatic conditions, experimental duration, and soil texture were the predominant factors controlling the changes in aggregation and aggregate‐associated SOC under NT. Overall, our results indicate that NT is an effective strategy to enhance soil aggregation and aggregate‐associated SOC, yet variations in responses are determined by specific environmental/agronomic factors. This study provided a basis for identifying site‐specific NT practice that could help improve soil structure and SOC sequestration, ultimately controlling soil degradation in croplands.